2024
DOI: 10.3390/su16093741
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Spatiotemporal Evolution Patterns and Coupling Coordination between Ecosystem Service Values and Habitat Quality in Diverse Scenarios: The Case of Chengdu Metropolitan Area, China

Gaoliu Huang,
Shiming Feng,
Chunguang Hu

Abstract: The global ecological decline resulting from urban development presents a significant challenge for numerous regions striving to reconcile conservation efforts with developmental needs. This study explores the relationship between ecosystem service value (ESV) and habitat quality (HQ) under various scenarios to elucidate prospective development trajectories. This study utilized the PLUS model to simulate land use patterns in the Chengdu metropolitan area across four distinct development scenarios. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Since the reform and opening up, Chinese cities have experienced rapid development. During the continuous expansion of urban areas, many natural ecological resources have been converted into urban construction land, severely damaging the diversity of the ecological environment, as confirmed by numerous studies [11,12]. Additionally, many studies have shown that impervious surfaces in cities easily cause local increases in the Land Surface Temperature (LST), while ecological lands such as forests, grasslands, and water bodies can mitigate temperature rises [13].…”
Section: Introductionmentioning
confidence: 98%
“…Since the reform and opening up, Chinese cities have experienced rapid development. During the continuous expansion of urban areas, many natural ecological resources have been converted into urban construction land, severely damaging the diversity of the ecological environment, as confirmed by numerous studies [11,12]. Additionally, many studies have shown that impervious surfaces in cities easily cause local increases in the Land Surface Temperature (LST), while ecological lands such as forests, grasslands, and water bodies can mitigate temperature rises [13].…”
Section: Introductionmentioning
confidence: 98%